Do monumento à escultura no campo expandido : três casos exemplares - Mateus, Andreia Filipa, 1990- (2016)
This dissertation proposes to study the concept of expanded field, developed by Rosalind Krauss, present in the work of three portuguese contemporary sculptors: Pedro Cabrita Reis, Fernanda Fragateiro and Rui Chafes. The study will be on the carvings, “Sem título”, “Jardim das “Ondas” and “Horas de Chumbo”, which are at the Parque das Nações ordered during the Grande Exposição Universal Expo’98, they presuppose an emancipated spectator. This feature combines the works of the three artists, though in diffrent ways, either by touch , memory, and the idea, respectively